2015
DOI: 10.1155/2015/896239
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Traceability Optimization and Shareholder’s Profit for Efficient Supply Chain Operation under Product Recall Crisis

Abstract: Product recall gains considerable importance in recent times; the reason may be the huge losses faced by manufacturers because of product recall issues. Furthermore, the revenue of the firm is immensely affected as a result of product recall, which may lead to serious outcomes. Huge recall cost (such as repairing or destroying the recalled products and cost of notification) occurs as a result of large recall. Therefore, in order to minimize the quantity and probability of recalls the traceability systems are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…• Multi-Objective Optimisation Methods (Hale and Moberg 2005 ; Merz et al 2009 ; Benaïcha and Hadj-Alouane 2013 ; Memon et al 2015 ; Zhang et al 2019 ; Laguna-Salvadó et al 2019 ; Ghorashi et al 2020 ; Khalilpourazari et al 2020 ; Malmir and Zobel 2021 ; Mosallanezhad et al 2021 ; Wang and Hu 2021 )…”
Section: Resultsunclassified
“…• Multi-Objective Optimisation Methods (Hale and Moberg 2005 ; Merz et al 2009 ; Benaïcha and Hadj-Alouane 2013 ; Memon et al 2015 ; Zhang et al 2019 ; Laguna-Salvadó et al 2019 ; Ghorashi et al 2020 ; Khalilpourazari et al 2020 ; Malmir and Zobel 2021 ; Mosallanezhad et al 2021 ; Wang and Hu 2021 )…”
Section: Resultsunclassified
“…In the 1994-2014 period, there only is one paper that develops a mathematical model, which introduces a detailed model to assess the economic impact of RFID (Bottani, 2009). For the 2015-2017 period, we find four papers using mathematical models (e.g., Memon, 2015;Faisal, 2016).…”
Section: Topic 6: Build-up (10%)mentioning
confidence: 99%
“…As such, managers have to balance the cost incurred by food quality risks and that of recall of products or the implementation of the traceability systems. Memon et al [111] proposed an integrated optimization model to minimize the expected loss to shareholders in recall crisis using batch dispersion methodology and taking into consideration recall costs. It is shown that higher traceability level decreases the stakeholders' losses due to recall but increases operational cost.…”
Section: Quantitative Models Of Food Traceability and Food Recallmentioning
confidence: 99%